Teacher Effectiveness and Use of Technology in Teaching - Amuthavalli, Prof. T.G.; Visweswari, Mrs. V. (International Journal of Advanced Science and Technology, 2019)
The paper  deals with teacher effectiveness of secondary school teachers in relation to use of technology. Survey method was employed for the study. The data was collected from 1200 secondary school teachers in Chittoor district of Andhra Pradesh state, India, through stratified random sampling technique. The self constructed teacher effectiveness questionnaire and check list for use of technology in teaching were used to collect the data.  Statistical techniques like mean, standard deviation and t-test were used for analysis. Results  show there is significant difference in teacher effectiveness whole tool  and temperament ,interpersonal relations, evaluation dimensions of  teacher effectiveness among secondary school teachers with reference to use of technology. It was also found that there was no significant difference among secondary school teachers in teacher effectiveness dimensions , Conceptual expertise, Class room management, Innovativeness with reference to Use of technology in teaching.